2016
DOI: 10.19071/rib.2016.v7.2863
|View full text |Cite
|
Sign up to set email alerts
|

Revealing contrasting genetic variation and study of genetic diversity in urdbean (Vigna mungo (L.) Hepper) using SDS-PAGE of seed storage proteins

Abstract: <p><strong>Total seed storage protein profiles of 20 urdbean genotypes including the popular variety T9 were analysed by Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). 14 genotypes could be clearly identified based on genotype-specific seed protein fingerprints while rest of the test genotypes were categorized into three protein types. Dendrogram based on electrophoretic data clustered the genotypes into seven groups at 78.5% phenon level.  TU 95-1 with TU 12-25-4 revealed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In addition, five polypeptide bands at molecular weight positions 63.0, 47.0, 39.0, 36.0, and 12.0 KD were found to be monomorphic. Tripathy et al (2016) reported that the genes controlling the expression of the monomorphic bands appeared to behave in single blocks. Rest of the 25 bands had shown polymorphism to the extent of 83.3% among the test genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, five polypeptide bands at molecular weight positions 63.0, 47.0, 39.0, 36.0, and 12.0 KD were found to be monomorphic. Tripathy et al (2016) reported that the genes controlling the expression of the monomorphic bands appeared to behave in single blocks. Rest of the 25 bands had shown polymorphism to the extent of 83.3% among the test genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Seed proteins are product of multigene families and are quite stable, uniform, reproducible and seldom affected by environmental fluctuations and management practices (Dunhill and Fowden 1965;Adriaanse et al 1969;Gray et al 1973;Basha 1979;Javaid et al 2004;Masoumi et al 2012;de Lumen 1990). They have sometimes provided better resolution of taxonomic and phylogenetic problems (Ladizinsky and Hymowitz 1979;Sathaiah and Reddy 1985;Panda et al 1986;Panigrahi et al 2007;Bianchi-Hall et al 1993;Lanham et al 1994;Singh et al 1991Singh et al , 1994Cherry 1975;Savoy 1976;Basha 1979;Klozova et al 1983a, b;Bertozo and Valls 2001;Liang et al 2006;Calbrix et al 2012;Malik et al 2009;Tripathy et al 2016;Emre 2009;Song et al 2016) in various plant taxa including Arachis. The present study, based on the data on total seed storage proteins and that of two fractions, including albumins and globulins, provides new and useful information regarding the evolution, diversification and genomic constitution of the taxa belonging to six of the nine sections of genus Arachis.…”
Section: Introductionmentioning
confidence: 99%